2011
DOI: 10.1080/15299716.2011.571985
|View full text |Cite
|
Sign up to set email alerts
|

The Decreasing Significance of Stigma in the Lives of Bisexual Men: Keynote Address, Bisexual Research Convention, London

Abstract: This article is constructed around a keynote address given at the Bisexual Research Convention, th Century Foundations of Homo/BiphobiaAlthough homosexuality had not previously been understood as a static sexual identity, this notion came to public consciousness with the conviction of English author, poet, and playwright, Oscar Wilde in 1895. His conviction, profoundly important toward our understanding of sexuality in the 20thCentury, event gave male homosexuals both a spokesperson and a flamboyant stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Other research has suggested that bisexual men are rated more negatively than bisexual women, gay men, or lesbians (Eliason, 2001). However, preliminary research suggests declining significance of homophobia and biphobia in men's lives today, with increased acceptance of bisexuality in sexual minority communities and within US and UK societies more generally (Ripley, Anderson, McCormack, Adams, & Pitts, 2011). Perhaps historically, sexual minority men were more accustomed to experiencing biphobia and were not as willing to discuss attractions towards women, whereas sexual minority men today might be more open about past, current and potential attractions to women.…”
Section: Psychology and Sexuality 13mentioning
confidence: 93%
“…Other research has suggested that bisexual men are rated more negatively than bisexual women, gay men, or lesbians (Eliason, 2001). However, preliminary research suggests declining significance of homophobia and biphobia in men's lives today, with increased acceptance of bisexuality in sexual minority communities and within US and UK societies more generally (Ripley, Anderson, McCormack, Adams, & Pitts, 2011). Perhaps historically, sexual minority men were more accustomed to experiencing biphobia and were not as willing to discuss attractions towards women, whereas sexual minority men today might be more open about past, current and potential attractions to women.…”
Section: Psychology and Sexuality 13mentioning
confidence: 93%
“…McCormack (2012b) has provided further evidence of the inclusion of sexual minority students in an ethnography of a religious sixth form. He showcases the stories of one lesbian, one gay, one bisexual and one transgendered student, drawing out the differences in their experiences, but nonetheless showing positive changes in their school experiences compared with research from previous decades (see also Ripley et al 2011). This is an accepted manuscript of an article published by Berghahn Journals in Boyhood Studies, available online at https://www.berghahnjournals.com/abstract/journals/boyhoodstudies/7/1/bhs070105.xml.…”
Section: The Inclusion Of Gay Male Peersmentioning
confidence: 98%
“…Gay was bantered about a bit by him and us, but he always maintained his bisexuality. Individuals who identify as bisexual often experience discrimination from both heterosexual and homosexual populations (Horncastle, 2008;Persson & Pfaus, 2015;Ripley, Anderson, McCormack, Adams, & Pitts, 2011;Roberts, Horne, & Hoyt, 2015). I was an ignorant ass.…”
Section: ***mentioning
confidence: 99%